A Proposed Framework For Redefining Smes In Malaysia: One Industry One Definition? - Hashim , Mohd Khairuddin; Abdullah, Mat Saad (Asian Academy of Management (AAM), 2000)
In Malaysia, small and medium-sized enterprises (SMEs) have been variously defined by different supporting agencies. These differences matter because the way an important concept such as SME is defined and interpreted has serious implications on the formulation as well as implementation of a particular policy (such as in identifying the qualified SMEs for assistance programmes). This paper initiates an attempt to provide a framework towards developing a ‘fair’ and ‘efficient’ definition of SMEs in the Malaysian context. This alternative approach is developed by taking into consideration not only the nature and needs of SMEs in Malaysia, but also by examining some of the widely used definitions available in literature. It is proposed that SMEs should basically be redefined according to the different types of industries. It is also advocated here that both quantitative as well as qualitative criteria be adopted in the framework for redefining an SME.